Visual cueing affects the processing of grammatical structure: A self-paced reading study on non-canonical word order in Bulgarian - Compensis, Paul (Proceedings of the Annual Meeting of the Cognitive Science Society, 2023)
Visual attention can influence how language is processed. For instance, previous research showed that visual cueing of a referent affects the choice of a particular grammatical structure. The present study extended this research to language comprehension and investigated whether visually cueing either the subject or the object of an event affects the interpretation of a textual event description in Bulgarian with either a subject-initial or object-initial word order. The presence of a visual cue matching the sentence-initial argument decreased self-paced reading reaction times and altered the accuracy in response to a comprehension question. Differences were found depending on the gender of the referent, highlighting the interaction of the visual cue and other linguistic information such as case marking. This study demonstrates that visually induced "context" can affect the linguistic salience of a referent in discourse and illustrates the interaction of domain-general cognitive mechanisms in language processin
Keywords: attention; reference; pronouns; differential object indexing